2021
DOI: 10.1038/s41598-021-90266-8
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study investigating food addiction in Parkinson patients

Abstract: Eating disorders (EDs) in patients with Parkinson’s disease (PD) are mainly described through impulse control disorders but represent one end of the spectrum of food addiction (FA). Although not formally recognized by DSM-5, FA is well described in the literature on animal models and humans, but data on prevalence and risk factors compared with healthy controls (HCs) are lacking. We conducted a cross-sectional study including 200 patients with PD and 200 age- and gender-matched HCs. Characteristics including c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Changes in the quality of the diet may be driven by specific cognitive changes pertaining to food selection or as part of an impulse control disorder, the latter of which may be related to dopaminergic medication (118) . Compulsive eating has been documented in PD, with one case–control study suggesting that 25 % of patients with PD consumed excessive energy compared with 12 % of healthy controls (119) . This can manifest as binge-eating and correlates with the presence of anxiety more strongly than medication type or dose (120) .…”
Section: Whole Body Metabolism In Parkinson's Diseasementioning
confidence: 99%
“…Changes in the quality of the diet may be driven by specific cognitive changes pertaining to food selection or as part of an impulse control disorder, the latter of which may be related to dopaminergic medication (118) . Compulsive eating has been documented in PD, with one case–control study suggesting that 25 % of patients with PD consumed excessive energy compared with 12 % of healthy controls (119) . This can manifest as binge-eating and correlates with the presence of anxiety more strongly than medication type or dose (120) .…”
Section: Whole Body Metabolism In Parkinson's Diseasementioning
confidence: 99%
“…As a sensitivity analysis, the meta‐analysis was repeated after excluding 5 studies 17 , 30 , 31 , 32 , 33 that included in the PD groups some patients with ICDs. Similarly, a statistically significant mean difference (2.85; 95% CI, 1.23, 4.46), with higher BIS‐11 total scores in patients with PD compared with control subjects emerged.…”
Section: Resultsmentioning
confidence: 99%
“…Only one article evaluated the relationship between FA and impulsivity in a 100% male sample [58] of individuals with obesity. Three further articles were identified that included a majority of men (10.3%) [49 In men, associations between FA and cognitive impulsivity, greater lack of planning, and weaker impulse control performance were found [58]. In the studies that had a higher percentage of men in their sample, FA was found to play a mediating role between impulsivity and BMI [56 One study did not detect FA in men [49••], while in another study, FA and impulsivity were not associated with the male gender [88].…”
Section: Impulsivity and Gender Differencesmentioning
confidence: 99%